Extracranial arteriovenous malformations: towards etiology-based therapeutic management - Julien Coulie; Emmanuel Seront; Miikka Vikkula; Laurence M. Boon (2025)
Anomalies during angiogenesis can initiate the formation of arteriovenous malformations (AVMs), characterized by aberrant connections between arteries and veins and fast lesional blood flow. These anomalies can manifest anywhere in the body, including the brain, and they typically appear at birth and evolve alongside growth of the individual. Depending on their location and size, AVMs can induce progressive deformation, chronic pain, functional impairment, and ulceration and pose life-threatening risks such as hemorrhage and organ dysfunction. The primary treatment modalities entail surgical intervention or embolization followed by surgery. However, these approaches are often challenging and seldom offer definitive resolution. In addition, inadequately performed surgery may trigger angiogenic rebound, fostering AVM recurrence. Advancements in comprehending the molecular pathways underlying AVMs have sparked interest in repurposing targeted therapies initially devised for cancer treatment. The first results are promising, giving new hope to the patients affected with these often devastating and debilitating lesions, the management of which presents major clinical challenges.